Leiomyomatosis Peritonealis Dissiminata - Hanne Christensen (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
The leiomyomatosis peritonealis dissiminata (LPD) a histologically benign condition, but it can residivere and be metastatic. Since the macroscopically picture imitates diffuse peritoneal carsinosis, the risk of unnecessary drastic precautions are nearby. Clinical Picture LPP is a multifocal tumor with a macroscopic image of multiple fi broids and subperitoneal nodules varying in size from 0.1 to 0.3 cm, histologically constructed of smooth muscle cells with fi broblasts. It is believed that Noduli is formed by metaplasic transformation of submesothelial stroma derived from the mulleric ductuli, induced and activated by changes in the body's oestrogen and/or progesteron ballance.